2018
DOI: 10.1210/jc.2018-00273
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Childhood Hyperthyroidism in France: A Nationwide Population-Based Study

Abstract: These findings shed light on the incidence of hyperthyroidism and the impact of sex on this incidence during childhood and adolescence. The observed incidence was higher than expected from the results published for earlier studies in Northern European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
1
14
1
5
Order By: Relevance
“…The proportion of boys in this study does not differ significantly from the proportions found in previous studies [8, 10, 12, 18] and it did not change between the first and the second 10-year study periods.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The proportion of boys in this study does not differ significantly from the proportions found in previous studies [8, 10, 12, 18] and it did not change between the first and the second 10-year study periods.…”
Section: Discussioncontrasting
confidence: 67%
“…They have shown an IR between 0.7 and 2.9/100,000 person-years in children <15 or 16 years of age in different European countries during 1982–2015 [13-18]. However, a much higher IR for Graves disease in children <15 years (6.5/100,000 person-years) during 1994–1998 has been reported in Hong Kong [19].…”
Section: Introductionmentioning
confidence: 99%
“…Such incidences were below 3 per 100,000 in Sweden ( 22 , 23 ), increasing over the years ( 23 ). In a French study, the number of cases of treated hyperthyroidism for Graves’ disease, due to Graves’ disease in 95% ( 18 ), also increased with age, being estimated at 7.89 per 100,000 among girls aged 10-14 years and 21.53 per 100,000 among girls aged 15-17 years ( 24 ). We found similar IR for thyroiditis of any type.…”
Section: Discussionmentioning
confidence: 99%
“…In a whole American paediatric population, the disease occurs with a prevalence of 1:10,000, compared to 1:1000 in adults ( 6 ). The onset of GD usually occurs during adolescence, and girls are 3–4 times more frequently affected than boys (<4 years of age, there is no sex dependence/predominance) ( 7 ). The second most frequent cause of hyperthyroidism is autoimmune thyroiditis (AIT), with its hyperthyroid phase termed hashitoxicosis.…”
Section: Epidemiologymentioning
confidence: 99%